Height, Health, and Cognitive Function at Older Ages - Case, Anne; Paxson, Christina (American Economic Review, 2008)
Research across a number of disciplines has highlighted the role of early life health and circumstance in determining health and economic outcomes at older ages. Nutrition in utero and in infancy may set the stage for the chronic disease burden that an individual will face in middle age (David J. Barker, 1998; Barker et al. 1989; Johann Eriksson et al. 2001). Childhood health may also have significant effects on economic outcomes in adulthood. Collectively, a set of childhood health measures can account for a large fraction of the explained variance in employment and social status observed among a British cohort followed from birth into adulthood (Anne Case, Angela Fertig and Christina Paxson 2005).